2021
DOI: 10.1093/ofid/ofab153
|View full text |Cite
|
Sign up to set email alerts
|

Viral Load Kinetics of Severe Acute Respiratory Syndrome Coronavirus 2 in Hospitalized Individuals With Coronavirus Disease 2019

Abstract: SARS-CoV-2 kinetics remain understudied, including the impact of remdesivir. In hospitalized individuals, peak sputum viral load occurred in week 2 of symptoms while peak viremia occurred within a week of symptom-onset, suggesting early systemic seeding of SARS-CoV-2. Remdesivir treatment was associated with faster rates of viral decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Nevertheless, our results do not indicate that remdesivir is ineffective, they indicate that the current dosing has room for improvement if toxicity allows. This is in line with clinical trials that report a shorter time to recovery [1,46], newer meta-analyses that support a slightly reduced mortality [7] and recent findings that the viral load declines more quickly in patients receiving remdesivir [11]. We therefore would like to argue for more dose-ranging and dose-fractionation trials.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, our results do not indicate that remdesivir is ineffective, they indicate that the current dosing has room for improvement if toxicity allows. This is in line with clinical trials that report a shorter time to recovery [1,46], newer meta-analyses that support a slightly reduced mortality [7] and recent findings that the viral load declines more quickly in patients receiving remdesivir [11]. We therefore would like to argue for more dose-ranging and dose-fractionation trials.…”
Section: Discussionsupporting
confidence: 83%
“…These are observation studies, but one can also, with some difficulty, investigate the impact of remdesivir on SARS-CoV-2 viral replication in host. While a modeling study from the French COVID Cohort Investigators, and French Cohort Study groups suggested remdesivir did not improve SARS-CoV-2 viral clearance time [9], the sample size was small, animal [10] and larger human studies [11] do show accelerated viral decay in remdesivir-treated macaques and humans, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that there is room for improvement in the dosing regimen is in line with clinical trials that report a shorter time to recovery [1,48], newer meta-analyses that support a slightly reduced mortality [7] and recent findings that the viral load declines more quickly in patients receiving remdesivir [11]. We therefore would like to argue specifically for more dose-ranging and dose-fractionation trials.…”
Section: Discussionmentioning
confidence: 62%
“…A modeling study from the French COVID Cohort Investigators and French Cohort Study groups suggested that remdesivir did not improve SARS-CoV-2 viral clearance time [9]. But their sample size was small, and animal [10] and larger human studies [11] do show accelerated viral decay in remdesivir-treated macaques and humans, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These models typically predict viral peaks within the first four or five dpi. However, SARS-CoV-2 peak viral load occurs later in the lung than in the upper respiratory tract (URT) [38], and the patient data have complex dynamics that last 15 to 30 dpi (Fig 6). Although the viral peak may be reached earlier in the URT, in the lung, it may not be achieved before the adaptive immune response begins [17].…”
Section: Simcov Viral Loads Compared To Patient Datamentioning
confidence: 99%